Carbon-dot-mediated co-administration of chemotherapeutic agents for reversing cisplatin resistance in cancer therapy - Feng, Tao (2020)
Chemotherapeutic DNA-modifying cisplatin and topoisomerase II (TOP2)-inhibiting doxorubicin (DOX) were co-administrated by full-color emissive carbon dots (CDs−Pt(IV)−DOX) through tumor intracellular environment responsive covalent bonds to successfully reverse the resistance of cisplatin in cancer therapy. Cisplatin was loaded in the form of cisplatin(IV) prodrug and DOX was conjugated via a pH-sensitive hydrazone bond. The internalization process of CDs−Pt(IV)−DOX by cancer cells could be monitored through multicolor emission from CDs and DOX. Upon uptake, cisplatin(IV) prodrug was activated to cytotoxic cisplatin under intracellular reductive condition, and the hydrazone bond was hydrolyzed to release DOX in intracellular weakly acidic environment. The released cisplatin and DOX exhibited combined anticancer effects via different mechanisms of action. Fluorescence imaging, a cytotoxicity study, and an apoptosis assay using CDs−Pt(IV)−DOX were performed to demonstrate the effective uptake and potent therapeutic efficacy toward A2780 and A2780cis cancer cells with cisplatin resistance. The developed CDs−Pt(IV)−DOX offers a promising fluorescent CD-based co-administration system for combating cisplatin resistance in cancer treatment.